Evaluation of Non-Governmental Organization (NGO) Partnership Schemes under the Revised National Tuberculosis Program (RNTCP) in Gujarat, India - Bhavesh Modi; Gaurav Desai (National Journal of Community Medicine, 2020)
Background: Government of India has started NGO schemes under RNTCP since 2001. However, there are no details available to show the impact or effectiveness of such interventions. The study was conducted to evaluate the NGO partnership schemes under RNTCP and to identify challenges and probable solutions for improvement of the same.